Efficacy of Andrographis paniculata, Psidium guajava and Piper betle as Prevention on Motile Aeromonad Septicaemia Infection in African Catfish (Clarias sp.) - D. Wahjuningrum; . Tarono; S.L. Angka (Jurnal Akuakultur Indonesia)
An effort to prevent Motile Aeromonad Septicaemia (MAS) disease in African catfish (Clarias sp.) performed using antibiotic was less safety and expensive ways.  An herbal medicine may be able to be a safety and cheap way to prevent of the MAS disease.  This study was conducted to determine efficacy of herbal medicine combination of sambiloto (Andrographis paniculata), daun jambu (Psidium guajava) and daun sirih (Piper betle). Herbal medicines were mixed to diet and fish were fed on the diet containing the herbal medicine for 7 days of rearing.  The dosage of herbal medicine per 100 gram of diet was PI (1.0 g sambiloto, 0.75 g daun jambu and 0.25 g daun sirih), PII (1.0 g sambiloto,  0.50 g daun jambu,  0.50 g daun sirih), and PIII (1.0 g sambiloto, 0.25 g daun jambu, and 0.75 g daun sirih).  On 8th day, fish were injected intramuscularly with 1 ml of Aeromonas hydrophila (105 cfu/ml) every 1 kg of fish.  Clinical symptom, feed response, fish weight, number of fish survive and visually changing of internal organs.  The results of study indicated that administration of herbal medicine A. paniculata, P. guajava and P. betle mixed into the diet effectively prevented A. hydrophila infection.  Combination of 1.0 gram A. paniculata, 0.75 gram P. guajava and 0.25 gram P. betle gave higher efficacy against A. hydrophila infection.